2019
DOI: 10.1002/pat.4548
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on wear and friction characteristics of phenolic composite coatings filled with different morphologies ZnO

Abstract: In this paper, different morphologies ZnO (disk‐like, rod‐like, and nanoparticles) were introduced into phenolic composite coatings to comparatively investigate the tribological properties. The structural and morphological characterization was conducted with Raman spectroscopy, X‐ray diffraction, and scanning electron microscopy. The tribological performances of composite coatings were evaluated using ring‐on‐block tester under dry condition at room temperature. Experimental results indicated that composite co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…[ 44 ] The variation trend of the special wear rate was shown in Figure 10(B). TiO 2 nanoparticles could be regarded as a stress transfer medium to prevent the stress from being transferred directly into the epoxy matrix, [ 16 ] which was beneficial to improve the fatigue resistance properties of the composites, leading to the decrease of the special wear rate compared to the special wear rate of the pure epoxy. However, with the increase of TiO 2 content, the special wear rate showed the first decrease and then increase, this was because the excessive fillers could destroy the continuity of epoxy composites and form the agglomerations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 44 ] The variation trend of the special wear rate was shown in Figure 10(B). TiO 2 nanoparticles could be regarded as a stress transfer medium to prevent the stress from being transferred directly into the epoxy matrix, [ 16 ] which was beneficial to improve the fatigue resistance properties of the composites, leading to the decrease of the special wear rate compared to the special wear rate of the pure epoxy. However, with the increase of TiO 2 content, the special wear rate showed the first decrease and then increase, this was because the excessive fillers could destroy the continuity of epoxy composites and form the agglomerations.…”
Section: Resultsmentioning
confidence: 99%
“…Bajpai et al [ 15 ] found that the tensile properties, fracture, and toughening mechanisms of the epoxy system were modified by rigid nanoparticles and their hybrids. Wu et al [16] found that the adding of different morphologies of ZnO significantly improved its friction and wear characteristics. Among the most nanoparticles, TiO 2 may be the most attractive on account of its properties, such as high chemical stability, super hydrophobicity, thermal stability, corrosion resistance, and great compatibility with various materials.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfuric acid was diluted with a ratio of (1:1), the samples were immersed with chemical solutions for different periods (7, 14, and 30) days where the samples were weighed before and after immersion. The wear rate was calculated at a different radius of wear disk and constant time according to the following relationship [11]:…”
Section: The Methods Of Workmentioning
confidence: 99%
“…More so, authors like Min et al, 104 Luong et al 105 and Ji et al 107 reported widely on the use of graphene 2-dimensional material 108 as reinforcement in enhancing the properties of polymer composites due to it high modulus of elasticity, high strength, and ultralow friction. Having pointed out the use of nanofillers such as carbon nanotubes, graphene and graphene oxide, silica, alumina, titania, boron nitride, carbon fibres, aramid fibres, and glass fibre as a reinforcement in improving the PI nanocomposite as presented in Table 1, recent researches have also utilized nanofillers such as Zinc oxide (ZnO), 110 Zirconium oxide (ZrO 2 ) 111 and silicon nitride (Si 3 N 4 ) 112 in enhancing the thermal, mechanical, and tribological properties of polymer composite. For instance Mu et al 113 reported on the effects of nano-ZnO loading on the mechanical and tribological properties of polytetrafluoroethylene (PTFE)/polyimide composite.…”
Section: Overview Of Polyimide Matrix Materials For Thermal Mechanica...mentioning
confidence: 99%